Effects of organic matter components and incubation on the cement-based stabilization/solidification characteristics of lead-contaminated soil. (December 2020) - Ge, Shangqi; Pan, Yize; Zheng, Lingwei; Xie, Xinyu
Abstract: Stabilization/solidification (S/S) has been studied since 1950s and widely used for the treatment of potentially toxic elements (PTEs). The coexistence of organic matter (OM) and PTEs can cause a very complicated mechanism for cement-based S/S applications and bring challenges from both scientific and engineering perspectives. To fill in the knowledge gap, this paper investigates for the first time the effects on S/S characteristics of OM components and incubation, which are the two main factors that result in the inconsistency in the leaching characteristics from the available studies. OM samples with different components (humic acid (HA) and fulvic acid (FA)) and contents were mixed into lead-contaminated soil and incubated for different durations of up to 90 days. The experimental results show that the strength of stabilized soils increases with increasing incubation duration and the lead leaching concentration of stabilized soils is decreased by 60.7%–83.6% from zero to 90 days. The lead leaching concentration of the HA group, which is 144.0% higher with no incubation than the non-OM group, becomes 58.3% lower with 90 days of incubation. The leaching concentration of the FA group remains much higher than those of the other groups. Finally, a competing mechanism of HA—weakening cement hydration reactions and stabilizing lead with a critical incubation duration of 14 days—is proposed, together with a cooperating mechanism of FA—weakening cement hydration reactions and releasing lead. Graphical abstract: Image 1 Highlights: The effects of OM on S/S characteristics depend on its components and incubation. With increasing incubation duration, lead leaching decreases, and UCS increases. HA has a competing mechanism affecting lead leaching, with a critical time. FA has a cooperating mechanism that results in the highest lead leaching. FA can weaken the UCS of stabilized soil more significantly than HA.